A machine learning approach to detect depression and anxiety using supervised learning - Ullas, Md Tahmidur Rahman; Begom, Mariyam; Ahmed, Anamika; Sultana, Raihan (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.